Wandering in Pakistan: The Paradoxical World of the Marginalized in Nadeem Aslam’s The Golden Legend (2017) - Firda Khoirunnisa; Ari Jogaiswara Adipurwawidjana; Sandya Maulana (Universitas Sanata Dharma, 2024)
This study explores the idea of place in Nadeem Aslam’s The Golden Legend (2017) to frame the identity crisis befalling the Christian community in Pakistan as a mirror of the similar experiences of marginalized groups in Britain. As a British novel expected to be read by Western readers, the depiction of the marginalization happening in Pakistan is utilized to allude to the condition outside the country: a paradox. The depicted paradox also recalls the history of Islam’s development in Türkiye and Spain, represented by the Hagia Sofia and the Great Mosque. The loss of ‘home’ causes the marginalized to wander in Pakistan, and, at the same time, they try to establish their identities and be remembered by society, both in the sense ofbelonging and of inhabiting memory. It is the same with the unsettled immigrant of Muslim Pakistanis, begging for their citizenship and being acknowledged in Britain. This analysis is based on Bhabha’s notion of unhomeliness and Derrida’s host and guest concept, composing an understanding that having no exact ‘home’, the Christian community being a guest to the Muslim community whose territory is obligated to preserve, is treated inappropriately. With these findings, we argue that wandering through places in Pakistan is an action determining whether one’s self is constructed or otherwise, illustrating Muslims in Britain having the same fate by remembering the golden legend told in the novel.